Antibacterial Activity of Fluorobenzoylthiosemicarbazides and Their Cyclic Analogues with 1,2,4-Triazole Scaffold - Urszula Kosikowska (Molecules, 2021)
The development of drug-resistant bacteria is currently one of the major challenges in medicine. Therefore, the discovery of novel lead structures for the design of antibacterial drugs is urgently needed. In this structure–activity relationship study, a library of ortho-, meta-, and para-fluorobenzoylthiosemicarbazides, and their cyclic analogues with 1,2,4-triazole scaffold, was created and tested for antibacterial activity against Gram-positive bacteria strains. While all tested 1,2,4-triazoles were devoid of potent activity, the antibacterial response of the thiosemicarbazides was highly dependent on substitution pattern at the N4 aryl position. The optimum activity for these compounds was found for trifluoromethyl derivatives such as 15a, 15b, and 16b, which were active against both the reference strains panel, and pathogenic methicillin-sensitive and methicillin-resistant Staphylococcus aureus clinical isolates at minimal inhibitory concentrations (MICs) ranging from 7.82 to 31.25 μg/mL. Based on the binding affinities obtained from docking, the conclusion can be reached that fluorobenzoylthiosemicarbazides can be considered as potential allosteric d-alanyl-d-alanine ligase inhibitors.